Dynamics of Land Ownership Rights in the Perspective of Indonesian Agrarian Law in the Perspective of Legal Certainty and Social Justice - Lily Kalyana; Widodo Budidarmo (JOSH: Journal of Sharia, 2025)
Land ownership rights are the strongest, fullest, and hereditary form of land rights in the Indonesian agrarian law system as regulated in the Basic Agrarian Law (UUPA) Number 5 of 1960. In its development, land ownership rights have experienced various dynamics influenced by legal, social, and economic factors. Changes in land-related regulations, such as the influence of the Job Creation Law and agrarian reform policies, have greatly affected land ownership and use in Indonesia. In addition, various problems such as legal uncertainty, agrarian conflicts, overlapping ownership, and land mafia practices have further complicated land ownership rights. Therefore, this study aims to analyze land ownership rights from the perspective of Indonesian agrarian law, examine the development of regulations related to land ownership, and identify challenges in the protection and implementation of land ownership rights. The analysis uses a normative juridical method with a statute approach and a conceptual approach. The legislative approach examines various regulations governing land ownership rights, including UUPA, Government Regulation Number 24 of 1997 concerning Land Registration, and other land policies. Meanwhile, the conceptual approach is used to understand the basic principles of agrarian law and its relevance in protecting land ownership rights. The research is supported by a literature study of various legal sources, such as academic journals and books related to land law. With this approach, this research is expected to provide a more comprehensive understanding of the dynamics of land ownership rights in the Indonesian agrarian legal system, as well as contribute to more equitable and sustainable land policy development.